Terrorism in Cyberspace - Krstić, Marko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2016)
This paper presents the research on the growing threat of cyber-terrorism, which needs to be addressed by this concept and tries to answer why terrorists carry out this type of activity. It seems that among the main motivations of terrorists is their use of the Internet for different aspects of the terrorist campaign, such as propaganda and recruiting. It will consider the different tactics they use and present the way in which the Internet has provided a new opportunity for terrorists in their implementation of the campaign, and how it was adapted to their needs. Cyber-terrorism is a new terrorist tactic in the expansion and use of information systems or digital technology, especially the internet, as an instrument of action or target, where they are a battleground for terrorists, where they are trying to use it as a means to improve their campaigns and attacks. It examines the potential threat of cyber-attacks by terrorist organisations and the ways in which they can use the internet and cyberspace to attack and thereby achieve goals similar to conventional physical attacks. As the developed societies increasingly rely on electronic communications, control systems and trade, the potential for terrorists to hit their target becomes an increasingly realistic possibility. Internet has become more a way of life and making it easier for users to become targets cyberterorism.